Reducing Myocardial Infarction by Combination of Irisin and Dendrobium nobile Lindl through Inhibiting Nod-Like Receptor Protein-3-Related Pyroptosis and Activating PINK1/Parkin-Mitophagy during Aging - Ding, Chen; Zhang, Chaofeng (Chinese journal of physiology, 2023)
Aging, a crucial risk factor for ischemic heart disease, has negative impacts on cardioprotective mechanisms. As such, there is still an unmet requirement to explore potential therapies for improving the outcomes of myocardial ischemia/reperfusion (IR) injury in elderly subjects. Here, we aimed to confirm the cardioprotective function of irisin/Dendrobium nobile Lindl (DNL) combination therapy against myocardial IR injury in aged rats, with a focus on the involvement of pyroptosis and mitophagy. Male aged Wistar rats (22-24 months old, 400-450 g; n = 54) underwent myocardial IR or sham surgery. Before IR operation, rats were pretreated with irisin (0.5 mg/kg, intraperitoneally) and/or DNL (80 mg/kg, orally) for 1 or 4 weeks, respectively, at corresponding groups. Cardiac function, lactate dehydrogenase (LDH) and cardiac-specific isoform of troponin-I (cTn-I) levels, the expression of proteins involved in pyroptosis (nod-like receptor protein-3 (NLRP3), apoptosis-associated speck-like protein, c-caspase-1, and GSDMD-N) and mitophagy (PINK1 and Parkin), and pro-inflammatory cytokines levels were evaluated after 24 h of reperfusion. Irisin/DNL combined therapy significantly restored cardiac function and decreased LDH and cTn-I levels. It also downregulated pyroptosis-related proteins, upregulated PINK1 and Parkin, and decreased pro-inflammatory cytokines secretion. Pretreatment with Mdivi-1, as mitophagy inhibitor, abolished the cardioprotective action of dual therapy. This study revealed the cardioprotective effects of irisin/DNL combination therapy against IR-induced myocardial injury in aged rats, and also showed that the mechanism might be associated with suppression of NLRP3-related pyroptosis through enhancing the activity of the PINK1/Parkin mitophagy. This combination therapy is worthy of further detailed studies due to its potential to alleviate myocardial IR injury upon aging.